2018
DOI: 10.1534/g3.118.200449
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Starvation PromotesCaenorhabditis elegansVulval Induction

Abstract: Studying how molecular pathways respond to ecologically relevant environmental variation is fundamental to understand organismal development and its evolution. Here we characterize how starvation modulates Caenorhabditis elegans vulval cell fate patterning – an environmentally sensitive process, with a nevertheless robust output. Past research has shown many vulval mutants affecting EGF-Ras-MAPK, Delta-Notch and Wnt pathways to be suppressed by environmental factors, such as starvation. Here we aimed to resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…Similar redundant relationships between redundant partners exist in many other contexts in the animal. Notably, the relative importance of Ras, Notch, and Wnt signals in vulva induction differ in various genetic backgrounds (Milloz et al, 2008; Gleason et al, 2002) and physiological conditions (Braendle and Félix, 2008; Grimbert et al, 2018), resulting in flexibility in the system. While vulval development in C. elegans, when grown under standard laboratory conditions, predominantly favors utilization of the EGF/Ras signaling pathway (Braendle and Félix, 2008), Wnt is the predominant signaling pathway in the related Pristionchus pacificus , which is ~250 MY divergent (Zheng et al, 2005; Tian et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similar redundant relationships between redundant partners exist in many other contexts in the animal. Notably, the relative importance of Ras, Notch, and Wnt signals in vulva induction differ in various genetic backgrounds (Milloz et al, 2008; Gleason et al, 2002) and physiological conditions (Braendle and Félix, 2008; Grimbert et al, 2018), resulting in flexibility in the system. While vulval development in C. elegans, when grown under standard laboratory conditions, predominantly favors utilization of the EGF/Ras signaling pathway (Braendle and Félix, 2008), Wnt is the predominant signaling pathway in the related Pristionchus pacificus , which is ~250 MY divergent (Zheng et al, 2005; Tian et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In certain vulvaless mutants with reduced signaling, starvation has been shown to restore vulval fates (Euling and Ambros 1996). A recent study demonstrated that loss of pept-1 was equivalent to starvation in suppressing the vulvaless phenotype caused by a partial loss-of-function allele in the lin-3/ EGF gene (Grimbert et al 2018) (see Upstream inputs to TOR signaling for discussion on pept-1). Moreover, let-363(RNAi) or rsks-1(2) also displayed significant suppression, albeit not as strong as that by pept-1(-).…”
Section: Roles Of Torc1 In Regulating Development and Behaviorsmentioning
confidence: 99%
“…Many other similar redundant relationships between redundant partners exist in the animal. Notably, the relative importance of Ras, Notch, and Wnt signals in vulva induction differ in various genetic backgrounds [6,65] and physiological conditions [111,112], resulting in flexibility in the system. While vulval development in C. elegans, when grown under standard laboratory conditions, predominantly favors utilization of the EGF/Ras signaling pathway [111], Wnt is the predominant signaling pathway in the related Pristionchus pacificus , which is ∼250 MY divergent [113].…”
Section: Discussionmentioning
confidence: 99%